Determinants of Distress Risk of Nepali Commercial Banks - Shahu, Dil Krishna (The Batuk, 2019)
This paper aims to examine the banks’ specific factors affecting distress risk. Using modified Altnan Z score as measure of distress risk, the study employed secondary data of 18 banks listed in Nepal Stock Exchange Limited for the study period from 2008 to 2014. The results show that the liquidity, profitability and size have the significant positive effect on z score indicating lower distress risk of firms. These results support the too big to fail doctrine and provides justification to increment of capital to 8 Arba by Nepal Rastra Bank. The study provides insight into the regulatory body and concerned authority of banks. Managers should make effort in maintaining the liquidity position of the bank and make effective strategy to earn higher profitability to avoid from being financially distressed.